Multimedia Technologies in the Internet of Things Environment, Volume 2 - Kumar, Raghvendra; Sharma, Rohit; Pattnaik, Prasant Kumar; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book proposes a comprehensive overview of the state-of-the-art research work on multimedia analysis in IoT applications. This is a second volume by editors which provides theoretical and practical approach in the area of multimedia and IOT applications and performance analysis. Further, multimedia communication, deep learning models to multimedia data, and the new (IOT) approaches are also covered. It addresses the complete functional framework in the area of multimedia data, IoT, and smart computing techniques. It bridges the gap between multimedia concepts and solutions by providing the current IOT frameworks, their applications in multimedia analysis, the strengths and limitations of the existing methods, and the future directions in multimedia IOT analytics.
Chapter 1. An Overview of Multimedia Technologies in Current era of Internet of Things (IoT) -- Chapter 2. A Deeper Look into Wind Powered IoT based Sustainable Organic Compost Machine -- Chapter 3. An Intelligent Music Recommendation Framework for Multimedia Big Data: a Journey of Entertainment Industry -- Chapter 4. A survey on Multimedia Technology and Internet of Things -- Chapter 5. The Latest Emerging Technologies In Big Data -- Chapter 6. Realtime accident detection and alarm generation system over IoT -- Chapter 7. Smart Automobile Health Monitoring System -- Chapter 8. Fault Detection And Data Management for IIOT -- Chapter 9. Theoretical and Instructional Aspects of Using Multimedia Resources in Language Education: A Cognitive View -- Chapter 10. Data mining techniques for producing clustering in Big Data with MapReduce function -- Chapter 11. Machine Learning Techniques for Biometric Fingerprint Recognition Using the Magnitudes to Provide Privacy and Integrity -- Chapter 12. Study and Develop an Effective Int faces to upload Data into Enterprise Resource Planning System. .
Keywords: Internet of things; Multimedia systems; Environment; Quantitative research; Internet of Things; Multimedia Information Systems; Environmental Sciences; Data Analysis and Big Data; Internet of things; Multimedia systems